P1151Impact of ARNI (LCZ696) on patients selection for ICD implantation in SCD primary prevention: a real-world experience. (18th June 2020) - De Ruvo, E; Cicogna, F; Bressi, E; Tota, C; Monzo, L; Mennuni, S; Bruni, G; Fagagnini, A; Borrelli, A; Scara, A; Panuccio, M; Grieco, D; et al.
Abstract: Background:  ICD implantation is recommended for primary prevention in patients with symptomatic NYHA II-III heart failure with reduced ejection fraction (< 35%) (HFrEF) and without left ventricle ejection fraction (LVEF) improvement despite at least three months of guideline-directed therapy. The use of angiotensin receptor-neprilysin inhibition with LCZ696 has shown to ameliorate left ventricle function and to reduce the ventricular arrhythmias burden in patients with HFrEF. Purpose: The profile of patients with HFrEF who may benefit from therapy with LCZ696 without further requiring an ICD in primary prevention is still unknown. We aimed to assess the prevalence of these patients and to find potential clinical predictors of responsiveness to this treatment. Methods:  We enrolled consecutive patients that started LCZ696 treatment for medical therapy optimization in the heart failure clinic of our institution. All of them were previously implanted with an ICD before LCZ696 availability (from 2009 to 2015). A cardiologist evaluated their home medications, clinical, and echocardiographic characteristics both at baseline (before starting LCZ696) and during follow up. The patients were grouped also according to the etiology of HF (ischemic/non-ischemic) and by gender. Patients were excluded if candidates to cardiac resynchronization therapy. Responsiveness to LCZ696 treatment was defined as an increase of LVEF to values > 35% at follow up (FU). Results: A total of 49 patients (67.1 ± 9.8 years of age) were enrolled in this study and followed in the heart failure clinic of our institution (mean follow up 11.5 ± 4.9 months). Among them, 19 patients (38%) showed an increase in LVEF to values > 35% at follow up and a significant improvement in LVEF was appreciated (baseline LVEF: 31.2 ± 4.5 vs. follow up LVEF: 35.4 ± 8.0; p 0.003). No significant differences were recorded at baseline in LVEF within HF etiology and gender groups. At follow up, we found a significant increase in post-therapy LVEF only in the non-ischemic etiology group (from 31.5 ± 4.4 to 37.1 ± 8.1, p = 0.001) and in the male group (from 31.4 ± 4.5 to 34.9 ± 7.9, p = 0.005) in comparison with the ischemic etiology and the female group, respectively. No significant statistical differences were appreciated between responders and non-responders neither in terms of home medications nor in the LCZ696 doses, both at baseline and follow up. Conclusion: This study suggests a potential impact of angiotensin receptor-neprilysin inhibition therapy in the selection of patients with HFrEF candidates to ICD in primary prevention. In this real-world experience from our HF clinic, we found a significant LVEF improvement in approximately 40% of patients treated with LCZ696. These patients, in FU evaluation, would not have needed for an ICD implantation. This benefit appears related to the non-ischemic etiology of HF and the male gender.